(untitled) (Research, Society and Development, 2022)
Livestock is one of the main activities of the Brazilian economy and pastures play a role in this scenario. However, external factors such as weeds tend to reduce the productivity, profitability and profitability of rural properties. The objective was to compare the control efficiency of three different herbicide dosages in an area predominantly infested by the species Mimosa debilis, Malva sylvestri, Kudzu lobata and Spermacoce latifolia in order to know which dosages would be viable to use without compromising the control efficiency. The experiment was carried out at the Federal University of Acre, between May and July 2018, in a completely randomized design with 4 treatments and 5 replications. The treatments were: T1: 0 ml dosage/spray, T2 (100 ml/20 L): 25 ml dosage/spray, T3 (200 ml/20 L): 50 ml dosage/spray and T4 (300 ml/20 L) : 75 ml dosage/spray. Weed population means were compared using the Tukey test (5%). T2 controlled 13.2% of the population and its use is not feasible. Between T3 and T4 there was no statistical difference (p<0.05) obtaining 95.4% and 98.2% of control efficiency, respectively. The use of the dosage of 200 ml/20L is the most viable to be used, observing the adequate control rate, reducing its incidence and improving the production of pastures allied to the fact of the lower cost-benefit ratio when compared to the dose of 300 ml/20 L of T4 pastures allied to the fact of the lower cost-benefit ratio when compared to the dose of 300 ml/20 L of T4.